2005
DOI: 10.1080/14034940510005897
|View full text |Cite
|
Sign up to set email alerts
|

Few middle-aged women with severe mental symptoms use psychotropic drugs: The Women's Health in Lund Area (WHILA) Study

Abstract: Mental symptoms were common among the participating women. The presence of severe mental symptoms was strongly associated with severe physical symptoms. Few women with severe mental symptoms used psychotropic drugs. Middle-aged women with severe mental symptoms need to be identified and provided with appropriate psychopharmacological, hormonal, and/or psychosocial treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
3
10
0
Order By: Relevance
“…We did not separate replies to questions on depression in this analysis but have previously shown that poor self-rated health is associated with treatment for depression (20), indicating that the Gothenburg Quality of Life instrument (21) used in the Women's Health in the Lund Area study is reliable. We have also shown that women who lived alone had a higher risk for severe mental symptoms (21). The present data are in line with previous results showing that living alone was associated with neglect of self-care in insulin-dependent diabetes (22).…”
Section: Risk Estimatessupporting
confidence: 82%
“…We did not separate replies to questions on depression in this analysis but have previously shown that poor self-rated health is associated with treatment for depression (20), indicating that the Gothenburg Quality of Life instrument (21) used in the Women's Health in the Lund Area study is reliable. We have also shown that women who lived alone had a higher risk for severe mental symptoms (21). The present data are in line with previous results showing that living alone was associated with neglect of self-care in insulin-dependent diabetes (22).…”
Section: Risk Estimatessupporting
confidence: 82%
“…The use of psychotropic drugs among people with mental distress or mental disorders has been studied both for institutionalized (114)(115)(116) and non-institutionalized populations (23,24,76,90,101,104,107,108,117).…”
Section: Factors Associated With Psychotropic Drug Usementioning
confidence: 99%
“…The basic questionnaire, distributed to all 6917 women, has been described in previous papers [12,15]. The response rate to the questions varied from 95.7%-100%.…”
Section: Methodsmentioning
confidence: 99%
“…Total alcohol intake was converted into grams of pure alcohol and number of drinks (12 grams of pure alcohol equals one drink). As in the previous papers alcohol consumption was divided into categories, while in this paper the level of risk consumption was lowered according to recent recommendations for women in Sweden [13][14][15]. Based on weekly alcohol consumption the subjects were grouped into:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation